Decomposition of inflation in Azerbaijan into supply and demand components according to supermarket data - Khazan Bakhshaliyev; Vugar Ahmadov (Graduate Institute of International and Development Studies, 2025)
The balance between supply and demand influences inflation and understanding whether one factor predominates the other has significant implications for economic policy. Distinguishing the contributions of supply and demand factors to inflation offers insight into the primary drivers of inflation during economic shocks and is especially important for monetary policymaking. Decomposition serves as a tool for testing theoretical frameworks and enables policymakers and practitioners to monitor the factors contributing to inflation in real-time. In this context, the paper aims to decompose inflation into supply- and demand-driven components using an alternative micro-founded approach. It relies on a fundamental theory of price formation: the relationship between price and quantity, based on monthly data for 2,559 goods sold in one of the largest supermarket chains in Azerbaijan from 2020 and 2025. For each item, a structural vector autoregression (SVAR) model is estimated individually, resulting in 2,559 SVAR models used to identify whether observed inflation is driven by demand or supply shocks. Preliminary findings from SVAR models highlight that demand is one of the main contributors to inflation, particularly in the post-COVID recovery period, which macro-founded models had previously underestimated. Consequently, this study contributes to the Central Bank of Azerbaijan by providing a tool to estimate the importance of demand-pulled inflation, helping policymakers stay ahead of the curve.
Keywords: E30; E31; E52; E58; 330; Supply and demand driven inflation; SVAR model; supermarket data